91.1k views
0 votes
8. (01.02)

Given that f(x) = x2 + 2x + 3 and g(x)
X+4.
3
solve for f(g(x)) when x = 2.
2
5
11
33

2 Answers

2 votes
The answer to this question is 51.
User Ona
by
5.2k points
4 votes

Answer:

51.

Explanation:

f(x) = x^2 + 2x + 3 and g(x) = x + 4.

f(g(x)) = (x + 4)^2 + 2(x + 4) + 3

= x^2 + 4x + 4x + 16 + 2x + 8 + 3

= x^2 + 8x + 16 + 2x + 11

= x^2 + 10x + 27.

x = 2.

f(g(2)) = 2^2 + 10 * 2 + 27

= 4 + 20 + 27

= 31 + 20

= 51.

Hope this helps!

User Yervand Khalapyan
by
5.2k points